The effects of international sanctions on green innovations - Fu, Qiang; Gong, Qiang; Zhao, Xin-Xin; Chang, Chun-Ping (Technological and Economic Development of Economy, 2023)
Since China is facing a complicated international situation and sustainable development requirement at the same time, this paper examines the effects of external uncertainty, international sanctions, on green innovations by adopting the system generalized method of moments (GMM) estimation for 30 provinces (autonomous region and municipalities) from 1997 to 2019. We employ green inventions as the dependent variable and 5 indicators of sanctions (including unilateral, plurilateral, multilateral, economic, and intensity) as the main explanatory variables alternately. For further robustness tests, we use substitution variable green utility models, adopt sub-samples in different regions, change the empirical methodology, and add omitted variables. We also examine the mechanism effects of three possible channels. The conclusion is that plurilateral and economic sanctions both present significant negative impacts on green innovations, whereas China was not affected by unilateral or multilateral sanctions during the sample period. GDP, interpersonal globalization, and environment are proved to be the possible channels through which sanctions affect green innovations. Our research findings should assist Chinese-listed companies suffering from sanctions to make better responses on their way to green innovations. First published online 24 November 2022